The Philosophical and Legal Rationale for a Systematic Analysis of Digital Dispute Resolution Models in Modern Arbitration - Ermakova, Elena (Տիգրան Մեծ)
In the article, the author presents a systematic analysis of models of digital dispute resolution in modern arbitration. The author studied the dispute resolution models on the platforms “Kleros”, “Aragon”, “CodeLegit”, as well as the Draft arbitration rules for smart contracts “JAMS-2018” and the English “DDRR-2021”. The author identifies the following types of models of arbitration dispute resolution: 1) traditional arbitration; 2) traditional arbitration with blockchain elements (a model based on the CodeLegit platform), 3) digital arbitration (“DDRR-2021”). The most important feature and difference of the English “Digital DR Regulation” 2021 is the fact that the entire process from the beginning (occurrence of the case) to the end (execution of the decision) is resolved automatically without the intervention of human arbitrators with the help of an artificial intelligence agent. This is the procedure for resolving a dispute in the field of smart contracts that should be called digital arbitration. The so-called “decentralized arbitration” on the platforms “Kleros”, “Aragon”, “OpenLaw”, “Mattereum Protocol”, “Rhubarb Fund”, “Jury. Online”, “Jur”, “OATH Protocol”, “Juris” and other models of this type does not allow these models to be considered arbitration. The author believes that these models should be conditionally called crowdsourcing quasi-arbitration.
Keywords: Philosophy of law